PERENCANAAN STRATEGIS TEKNOLOGI INFORMASI PADA SMAIA 4 KEMANG PRATAMA - Oryza Gilang H.; Widya Apriliah; Mohammad Syamsul Azis (Swabumi, 2015)
trategies in planning the right information systems can support the development of businessprocess activities, objectives, vision and mission the Agency can even add value to such acompetitive advantage in the face of similar competitor with institutions. SMAIA 4 KemangPratama is a formal private education institutions. However, SMAIA 4 Kemang Pratama hisbusiness activities in the process still not fully optimized system of information has not been fullyintegrated. To get the information systems strategy planning, then the researcher using the methodof SWOT analysis, Value Chain and PEST. The purpose of this research is to produce a strategyMaster Plan of information systems and information technology to realize the vision, the Missionof the institution and to improve the quality of education in the face of competitors with similarSMAIA 4 Kemang Pratama and the need for qualified human resources in the current era.